Uterus-like mass: A very rare and elusive entity a case report. Issue 39 (September 2016) - He, Jian; Xu, Jie; Zhou, Hong-Yan
Abstract: Background: Uterus-like mass (ULM) is an extremely rare lesion. Gross morphology of ULM resembling a uterus. It can occur in various organs in the abdominal cavity, even in the spinal cord. The histogenesis of ULM remains uncertain. A number of hypotheses have been proposed including metaplasia, congenital anomaly, and heterotopia theory. Methods: We describe a case of 43-year-old male presented with a complaint of acute low abdominal pain. Pelvic ultrasound found a large pelvic mass embedded in the broad ligament. Results: The mass contains a variable thickness smooth muscle layer lined with endometrial glands and stroma which resembling a uterus. Eventually, the patient was diagnosed as ULM by histopathological examination. Conclusion: Except hypomenorrhea, the patient did not have any other associated abnormalities. We suggest this case supports the metaplasia theory that ULM is a benign mass formed by the proliferation of ectopic endometrial stromal cells or pluripotent mesenchymal cells of the 2nd Müllerian system.